Modification of The Headman Role on Increasing Knowledge and Attitudes About Breastfeeding and Complementary Food in A Remote Island - Epti Yorita; Dahrizal; Sahidan; Mely Gustina; Yulinda (Media Gizi Indonesia, 2023)
One of the health program's priorities is to reduce the incidence of stunting. Interventions currently being carried out focus on the first 1000 days of life. However, they have not been successful due to difficult access, educational, socio-economic and cultural factors, such as on the remote island of Enggano. Therefore, cultural-based intervention is needed with local communities as the perpetrators because it is the social capital of development. This study aims to determine the influence of the role of the traditional Paabuki leader and cadres on knowledge and attitudes about breastfeeding and complementary food in children under two years old on Enggano Island, North Bengkulu Regency, in 2021.This research uses a quasi-experimental research design without a control group. The intervention was in the form of modifying the role of traditional Paabuki leaders and cadres in training. Samples were 40 women with children under two years old selected by purposive sampling. The research results on the role of Paabuki and cadres affected knowledge and attitudes about breastfeeding and complementary food with a p-value = 0.00. However, they did not affect breastfeeding behavior and complementary food with a p-value =1. Parity is the most influential factor in knowledge and attitudes about breastfeeding and complementary feeding (p-value =0.01). The role of Paabuki and cadres can be modified as channel media in providing information and advocacy about breastfeeding and complementary food. Service providers must carry out program innovations based on local culture so that the community more easily accepts them.